Cystosarcoma Phyllodes of the Seminal Vesicle: A Case Report and Literature Review - Lucio Olivetti; Francesco Laffranchi; Vincenzo De Luca (Case Reports in Urology)
Cystosarcoma of the seminal vesicle is a very rare malignant tumor; in the literature only four cases are reported. We present a case of cystosarcoma phyllodes arising in the right seminal vesicle of a 49-year-old man without any urinary symptom but with persistent constipation. Ultrasound examination showed a mass at the right superior base of the prostate subsequently studied with CT and MRI. The patient underwent vesiculectomy; his postoperative course was uneventful. The patient is still well, without evidence of recurrent disease.